Pengetahuan Self-Monitoring Gizi Remaja dan Asupan Makronutrien: Implikasi Untuk Penguatan Edukasi Program Uks - Zuly Daima Ulfa; Jeff Agung Perdana; Arief Nur Wahyudi (Universitas Pahlawan Tuanku Tambusai, 2026)
Adolescents are vulnerable to imbalanced intake and poor diet quality, therefore, education is needed in the school context through nutrition self‑monitoring skills within the School Health Unit (UKS). This study examined the association between adolescents’ self-monitoring nutrition knowledge and energy–macronutrient intake derived from multi-day food records collected using the FatSecret app, and its implications for UKS strengthening. A cross-sectional analytic study was conducted at MA Darul Ulum Palangka Raya (river-basin/DAS area) in December 2025. Knowledge was assessed using a 15-item Likert questionnaire (physical activity, food logging/nutrition, and sleep–energy domains). Energy and macronutrients were calculated as each participant’s mean daily intake from multi-day diaries; the main analysis included ≥3 recording days (n=24) and sensitivity analysis included ≥2 days (n=27). Recorded fruit–vegetable intake was low (vegetables 12.2±19.0 g/day; fruit 33.1±47.2 g/day), and 33.3–37.0% recorded none during monitoring. The total scale showed good internal consistency (α=0.831–0.828). Total knowledge was associated with energy intake (Main ρ=0.461; p=0.023; Sens ρ=0.487; p=0.010). In adjusted linear regression, food logging/nutrition knowledge was associated with percent energy from fat (B=5.33; p=0.049), while the number of recording days was inversely associated (B=-1.34; p=0.042). Findings support UKS education emphasizing consistent logging and macronutrient composition literacy.